Proceso de atención de enfermería en paciente de 22 años de edad con traumatismo craneoencefálico. - Valles Salazar, Kevin Alexis (2020)
Head trauma is a functional deterioration of the cranial content caused by a sudden exchange of mechanical energy, causing concussion, contusion, hemorrhage or lacerations of the brain. The severity of the trauma will depend on the type of injury. Arguello (2018). In developed countries there is a percentage of 40 to 60% of the cases, and the developing country has an incidence of 80%, the severity of the injury can be determined by measuring the levels of consciousness using the Glasgow like scale divided into severe, moderate and mild (Valarezo Chuchuca, 2004). The present clinical case was developed with the purpose of applying the nursing process in a 22-year-old male patient with a diagnosis of head trauma, to obtain the patient's information through subjective and objective data that allow knowing the causes that allow know the causes and consequences of this trauma, in order to determine the risk factors and complications and then analyze the patient's results.